Pengaruh Gaya Kepemimpinan Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT. Angkasa Pura I Cabang Bandar Udara Internasional Sultan Hasanuddin Makassar Divisi Operasional - Saputra, Faisal Andri; Hamid, Muh Zulkifli (Movere Journal, 2025)
This study aims to analyze the Influence of Leadership Style and Environment on Employee Performance at PT. Angkasa Pura I, Sultan Hasanuddin International Airport Branch, Makassar, Operational Division. The research method used is quantitative research which aims to describe and analyze the influence of leadership style and work environment on employee performance at PT Angkasa Pura Makassar. The population of this study is all employees working at the PT Angkasa Pura Makassar office in the Operational Division, totaling 80 people. The sample in this study was 80 people. In this study, primary data collection. Based on the results of the research conducted, conclusions can be drawn regarding the influence of leadership style and work environment on employee performance, it can be concluded that leadership style and work environment have a significant effect on employee performance at PT. Angkasa Pura I, Sultan Hasanuddin International Airport Branch, Makassar, Operational Division.